Nurturing Psychological Sensitivity in Early Childhood : Preparing Young Minds for the Challenges of Artificial Intelligence - Nurmawizatillah (VIRTUOUS JOURNAL, 2024)
The rapid advancement of artificial intelligence (AI) is transforming the cognitive, social, and emotional landscapes in which children grow and develop. This paper examines the importance of nurturing psychological sensitivity in early childhood as a foundational strategy for preparing young minds to navigate the complexities of an AI-driven world. Psychological sensitivity, understood as the capacity for emotional awareness, empathy, adaptability, and reflective thinking, is increasingly essential in an era where human-machine interaction is pervasive. Using a qualitative and interdisciplinary approach, this study integrates insights from developmental psychology, education, and digital culture to propose a framework for cultivating psychological sensitivity in early childhood. The findings suggest that early emotional attunement, guided play, ethical digital exposure, and value-based education play critical roles in developing resilient and adaptive children. Furthermore, the study argues that psychological sensitivity functions as a protective factor against the potential dehumanizing effects of excessive AI reliance. This research contributes to contemporary educational discourse by offering a holistic model that bridges early childhood development with emerging technological challenges.